Computational neuro-physiological model (CNP) to profile lower primary school students in inclusive education: a concept paper - Md Nor, Norzaliza; Zakaria, Noor Azura; Azuddin, Muna; Mahmud, Murni; Abdul Rahman, Abdul Wahab; Abdul Karim, Ruwinah (The World Academy of Research in Science and Engineering, 2021)
Inclusive education (IE) is commonly accepted internationally as a standard right for all children. Malaysia has similar aspiration to implement the concept in the school system. However, it appears IE is challenging for parents, teachers and students. One of the challenges is to produce a well-trained and competent teacher to recognize learning abilities and disabilities of individual students. The Malaysian government is committed to ensure children to receive equality in education. Malaysia Education Blueprint (MEB) spells out 75% of children with learning disabilities must be part of IE by 2025. There is a gap in IE studies in terms of investigating the relationship between emotions and learning ability among students in IE environment. Therefore, this concept paper proposes a standard profiling model by using the Computational Neuro-physiological (CNP) model to profile lower primary school students in IE. This paper also emphasizes the possible use of EEG technology in detecting the emotion, behavior and mental state that can be used to indicate the student’s learning ability in the inclusive education. This research is important to be carried out to have a student's profile which can be used to facilitate teachers to improve their competencies in teaching and handling the students